Perceived index of the environmental quality and environmental stress in students of the UNMSM - Hernández Valz, Héctor M. (2004)
OBJECTIVE: To relate the perceived index of the environmental quality to environmental stress in students of the UNMSM - Peru. DESIGN: Descriptive corelational with an intentional sample of 200 subjects. MATERIAL And METHODS: The semantic differential was used to measure both variables. 5 aspects of the atmosphere were moderate selected by the sample: the green sweepings, areas, the smog, the transit, the security, being the considered SMOG most serious. RESULTS: Was an equal index PEQI to 3.82, slightly satisfactory. The level of measured environmental stress was of an average of 3.45, little satisfactory. CONCLUSIONS: Both results little indicate a good relation with the surroundings. The relation between both variables has an equal r to 0.62, is to say that it is significant.